STRATEGIC IMPLICATIONS OF THE CRISIS ON NIGERIA’S ECONOMY AND NATIONAL SECURITY - Adewale , Oladipo Oyekanmi (Multi-Disciplinary Research and Development Journals Int’l, 2026)
The Middle East crisis has continued to shape global economic and security dynamics, with far-reaching implications for developing economies such as Nigeria. This paper examines the strategic implications of the crisis on Nigeria’s economy and national security, focusing on oil price volatility, inflationary pressures, energy security challenges, exchange rate instability, security threats, and emerging geopolitical opportunities. Using a qualitative review of relevant local and international media reports and policy analyses, the study finds that while rising oil prices may temporarily boost Nigeria’s revenue, the broader consequences such as increased cost of living, weakened macroeconomic stability, and heightened security risks pose significant challenges. The paper concludes that Nigeria remains highly vulnerable to external geopolitical shocks due to structural weaknesses in its economy and security systems. It recommends urgent policy actions, including economic diversification, energy sector reforms, strengthened security frameworks, and proactive foreign policy engagement, to mitigate risks and harness potential benefits arising from global crises.